THE EFFECT OF ADDITION OF CITRIC ACID AT DIFFERENT CONCENTRATIONS ON THE CHARACTERISTICS OF REBON SHRIMP (Mysis relicta) PROTEIN ISOLATES - Suryo, Joko; Suparmi, Suparmi; Sumarto, Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTÂ This study was aimed to obtain the best product ofrebon shrimp(Mysis relicta)Â  protein isolates by addition of citric acid at different concentrations. The parameters observed were the amount of flour yielded and the proximate chemical composition (the content of moisture, ash, fat and protein). The method used was an experimental and the design used was a Completely Randomized Design (CRD). The treatment conducted was addition of citric acid solution at 3 different level concentrations (3.5%, 4%, and 4.5%). The results showed that the best rebon shrimp protein isolates was produced by adding 4.5%citric acid. The protein isolate was containing 4.11%water, 19.82%ash, 2.11%fat and 84.20% protein. Meanwhile, the content of total amino acid was 39.65%, dominated by leucine, glutamic acid and aspartic acid at 9.03%, 5.09%, 4.20%, respectively.Keywords: citric acid, isolate protein, proximate